Indonesia Membership on Asia-Pacific Space Cooperation Organization (APSCO): Cost and Benefit Analysis - Husni Nasution; Shinta Rahma Diana; Bernhard Sianipar; Sri Rubiyanti; Dini Susanti; Astri Rafikasari (Jurnal Hubungan Internasional, 2018)
Indonesia with seven other countries, namely Bangladesh, China, Iran, Mongolia, Pakistan, Peru, and Thailand are the signatory countries of APSCO Convention, on October 28th, 2005. APSCO is space coopeation organization outside the United Nations system for the Asia Pacific region, initiated by the People’s Republic of  China. To date, from the eight signatory countries, only Indonesia has not ratified yet and has not become a full member of APSCO. This paper examines cost and benefit of the Indonesia membership on APSCO.  The methods used are quantitative and qualitative method.  While the analysis used approaches related to contribution of cost to provided and benefits to be received by Indonesia as well as the national interest mentioned in Presidential Decree No. 64/1999 on Indonesian Membership and Indonesian Government Contributions to International Organizations.  From the study, it was found that by ratifying the Convention and following APSCO activities optimally, the benefits will be receive by Indonesia greater than contribution given to APSCO. Similarry, the joining of Indonesia in APSCO will also provide substansial benefit for the national interest, especially for politic, economic, international peace and security, humanity, and others as well as  enhancing better relationship among countries in the Asia-Pacific region.